The power of syndication: The innovation output of venture capital investments in the United States - Shuwaikh, Fatima; Dias, Joakim (Management international / International Management / Gestiòn Internacional, 2023)
This paper demonstrates the impact of the participation of corporate venture capital (CVC) funds and independent venture capital (IVC) funds in syndicated investments. We examine the dynamics of the impact of these syndications and the channels (industry fit and location fit) that improve innovation effectiveness. Based on the main sample of 5182 US. funded companies between 1998 and 2017, there is strong evidence of an existing superiority of CVC engagement in syndications (CVC/IVC) that can further boost the innovation output contribution. Additionally, the results show that industry and location fit augment the innovation output of the entrepreneurial companies.